The answer is A because opposite angles are the same. Therefore, 1 and 2 are congruent because their angle sizes are exactly the same.
<h3>✽ - - - - - - - - - - - - - - - ~<u>Hello There</u>!~ - - - - - - - - - - - - - - - ✽</h3>
➷ 1) (3(3) + 4.5) - |-5| = 8.5
2) (4(5) - (15)^2 = 25
3) (2)^3 - 6 - 4 = -2
4) 3(-10) - 5(6) = -60
5) 6 + 1/2(10 + 8) = 15
6) square root of (4 + (6 x 5)) = 5.830951895
<h3><u>
✽</u></h3>
➶ Hope This Helps You
➶ Good Luck
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
Answer:
g=28
Step-by-step explanation:
g + (-7) = 21
g-7 = 21
g= 21+7
g=28
Answer: C
Step-by-step explanation:
Answer:
sum of 2ab2 and (-5ab2) =
-3ab2
-3ab2=(-6ab2)+ x
x= -3ab2+6ab2
= 3ab2
thus, 3ab2 is ur ans
Step-by-step explanation: